Awareness, attitudes, and beliefs about music-induced hearing loss: Towards the development of a health communication strategy to promote safe listening. Issue 8 (August 2019) - Diviani, Nicola; Zanini, Claudia; Amann, Julia; Chadha, Shelly; Cieza, Alarcos; Rubinelli, Sara
Highlights: 1.1 billion young people risk developing hearing loss due to unsafe listening. This study aims at identifying modifiable factors that influence listening habits. Four factors were identified that can be addressed in a communication campaign. Enforcement of policies is needed to ensure success of the campaign. The campaign should be informed by the principles of social marketing. Abstract: Objective: Worldwide, 1.1 billion young people are at risk of developing hearing loss due to unsafe listening. The World Health Organization plans a global health campaign to promote behavior change. In an effort to develop effective evidence-based interventions, this study identifies modifiable factors that influence listening habits. Methods: Online survey among 1019 individuals aged 18–35. The questionnaire was based on theories of behavior change. Results: Individuals not contemplating change showed a lack of knowledge, tended not to feel particularly at risk, and did not see the benefits of preventive measures. Conversely, those considering a change perceived more barriers (e.g., lack of information on how to act, ). Self-efficacy was shown to play an ambivalent role. Conclusion: Four factors that can be influenced by a health communication intervention were identified: risk perception, perceived safe listening level due to a lack of symptoms, knowledge, and perceived benefits and barriers, in particular perceived loss of pleasure. Practice implications: The first aspects can be influenced through health communication interventions. Influencing the perceived loss of pleasure additionally requires an analysis of competing pressures. To support and not exceedingly burden the individual, we further suggest to address environmental aspects (e.g., policies).